Reframing ESP Learning Through Interpersonal Intelligence: Promoting Engagement and Disciplinary Relevance in Islamic Higher Education - Sahril; Nurasia Munir; Fatima; Nurfauziah Mansur (Eduvelop: Journal of English Education and Development, 2026)
English for Specific Purposes (ESP) plays a crucial role in preparing students of Islamic Library and Information Science (ILIS) to access global resources, understand international cataloguing standards, engage with digital information systems, and participate in global academic discourse. However, students’ interest in English learning in many Indonesian Islamic higher education institutions remains limited, often due to language anxiety, limited exposure, and perceived irrelevance to their disciplinary identity. This study seeks to investigate the potential for pedagogical integration of interpersonal intelligence into ESP instruction with the aim of raising student engagement and the subject matter relevance in English learning. Adopting a qualitative case study design, the research was conducted in an ILIS English classroom at UIN Datokarama Palu. Data were collected through classroom observations, semi-structured interviews with 18 students, and analysis of instructional documents. The data were analysed using thematic analysis involving open, axial, and selective coding procedures, with methodological triangulation to ensure credibility and analytical rigor. The findings reveal that interpersonal intelligence-based strategies such as peer collaboration, dialog interaction, group problem solving, and socially mediated feedback significantly increase students’ engagement, self-confidence, and willingness to use English, as well as create a positive learning environment. More significantly, embedding ILIS specific disciplinary tasks within collaborative activities strengthens students’ professional identity and situational relevance awareness, thereby transforming English learning into a socially mediated and career-oriented practice. This study contributes to ESP scholarship by proposing an identity-integrated interpersonal framework that connects socio-emotional interaction with disciplinary discourse practices. Although limited to a single institutional context, the findings offer empirical insight into how socially constructed ESP environments can sustain engagement and professional readiness in Islamic higher education settings.